Sepsis-Induced Coagulopathy as a Risk for Postoperative Arterial Thrombosis: A Case Report - Dewi Swastikasari; Septian Adi Permana (JAI (Jurnal Anestesiologi Indonesia))
Background: Venous thromboembolic disease and arterial thrombosis are recognized as common causes of hospital mortality, especially in postoperative patients, those who are immobilized, and individuals with sepsis. Coagulopathy is a significant factor due to the interaction between inflammation and coagulation, stemming from widespread endothelial damage.